2012
DOI: 10.1007/s11605-012-1827-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Histopathological Features of Primary Colorectal Cancers that Predict Lymph Node Metastases

Abstract: No single histopathological feature of colorectal cancer reliably predicted lymph node metastases. Several risk factors that correlate highly with nodal disease are not routine components of standard pathology reports. Until further research establishes histopathological or molecular patterns for predicting lymph node spread, caution should be exercised when basing treatment decisions solely on these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
70
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 79 publications
1
70
1
Order By: Relevance
“…3,4 Tumor budding at the invasive tumor margin is an established negative prognostic factor in resected colorectal cancer. [5][6][7][8][9][10][11][12] Widespread use of tumor budding as a prognostic factor has been impeded by a lack of standardized histopathological criteria, highlighted recently by Mitrovic et al 13 who state that 'although performing a tumor bud count is easy in theory, deciding what is or is not a bud can prove surprisingly difficult in practice'. Recent studies have addressed the role of tumor budding in resected colorectal specimens.…”
mentioning
confidence: 99%
“…3,4 Tumor budding at the invasive tumor margin is an established negative prognostic factor in resected colorectal cancer. [5][6][7][8][9][10][11][12] Widespread use of tumor budding as a prognostic factor has been impeded by a lack of standardized histopathological criteria, highlighted recently by Mitrovic et al 13 who state that 'although performing a tumor bud count is easy in theory, deciding what is or is not a bud can prove surprisingly difficult in practice'. Recent studies have addressed the role of tumor budding in resected colorectal specimens.…”
mentioning
confidence: 99%
“…A wealth of original studies, systematic and meta-analysis reviews have been published on the subject of lymphatic vessel invasion (LVI) [5-7], lymphatic vessel density (LVD) [8-10] and tumour budding (TB) [11-15] in CRC prognosis [16,17]. A number of these have concentrated on early stage disease and the ability to utilise histopathological features to predict lymph node metastasis or to stratify patients at high risk of disease recurrence and poor outcome [6,9,16,18-22].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, tumor budding at the invasive front has been recognized as a strong predictor of lymph node involvement, distant metastasis, local recurrence, and poor disease-free survival 60-63. However, a recent meta-analysis of 76 selected articles from 602 citations concluded that: (1) “no single histopathological feature of colorectal cancer reliably predicted lymph node metastases, and (2) several risk factors that correlate highly with nodal disease are not routine components of standard pathology reports” 64. More importantly, tumor budding at the invasive front is primarily, if not solely, seen at the invasive stage of disease, which is often beyond the point where surgery alone is curative.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, detection of tumor budding at the invasive front is unlikely to have significant value for early detection and intervention of CRC metastasis. Similarly, no other immunohistochemical feature can reliably predict the invasive or metastatic potential of a given CRC or identify the specific individuals with pending or at increased risk for metastatic CRC 64.…”
Section: Introductionmentioning
confidence: 99%